STRENGTHENING LITERACY THROUGH LIBRARY REVITALIZATION AND READING TREE INNOVATION - Arafah Mazaya; Rika Mutiara (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to improve students' literacy culture through library revitalisation and the development of literacy media, including "Reading Tree," a program designed to encourage reading, and "My Reflection Paper," a tool for students to express their thoughts on what they read. The background to this activity stems from low student interest in reading and the library's suboptimal layout. Implementation methods included reorganising the library, grouping books by category, creating visual literacy media, and conducting reading activities that concluded with student reflections. The results of the community service program indicate that the library has become more comfortable, structured, and engaging for students. The implementation of "Reading Tree" generated enthusiasm, as evidenced by the large number of students who attached "leaves" as a token of appreciation for reading. Meanwhile, analysis of "My Reflection Paper" indicates that the program fosters students' metacognition, creativity, and comprehension. Student reflections demonstrate increased enjoyment, curiosity, and the ability to summarise reading content. This program has proven effective in strengthening reading interest and building a sustainable literacy culture.